Light Pollution Mapping in Pécs City with the Help of SQM-L and VIIRS DNB. The Effect of Public Luminaire Replacements on the Sky Background of the Urban Sky - Gyenizse, Péter; Soltész, Emese; Kovács, János; Nagyváradi, László; Elekes, Tibor; Gyenizse-Nagy, Sára Bodza; Németh, Gergő; Halmai, Ákos (Geographica Pannonica, 2022)
Recently light pollution has been one of the most dynamically increasing form of environmental pollution. Light, if it arrives at the wrong place, time, quantity and quality, is harmful to human health and the physical environment – not to mention that it is a mere waste of energy. The brightness of the sky above Pécs was measured by SQM-L instruments in 2011 and 2019. Maps of the different neighbourhoods with different levels of light pollution have been prepared. In addition, special VIIRS day/night band satellite images were also analysed using QGIS software. Our investigations coincided with the modernization of street lighting in the city. The impact of LED illuminators installed along main roads in Pécs was observed locally.
Keywords: light pollution mapping; SQM-L; VIIRS day/night band; QGIS; TIN; Thiessen polygon; Pécs